Hierarchical Model for Optimizing Natural Fiber Selection Process for Eco-design of Buildings - Balo, Figen; Sua, Lutfu S. (Taylor & Francis Inc, 2022)
The composites based on fiber are commonly used in the high performance building materials. The composites mostly use petro-chemically derived fibers like polyester and e-glass due to their beneficial material properties like high stiffness and strength. All the same, these fibers also have important shortcomings related to energy consumption, recyclability, initial processing expense, producing health hazards, and sustainability. Rising environmental awareness along sustainable building technologies is driving the research, development and utilization of green building materials, especially the development of bio-based materials depend on renewable, natural materials. In this paper, the natural fiber evaluation approach is applied, which covers a lot of criteria. Comparative assessment of diverse natural fiber types is conducted by using a hierarchical decision-making approach. Multi-criteria decision-making methodologies are appropriate for making decision and assessing for the most proper options in order to select the excellent criteria. This includes a group of investigation methods, which contemplates problems in decision-making. The best performing fiber choice is made by comparatively evaluating the materials related to green building. The proposed fiber can be used and applied by green building materials manufacturing companies in various countries or locations as a reference when selecting the fiber with best performance.
Keywords: Natural Fiber; Hierarchical decision-making; Sustainability; Green building; Renewable material